A role for endothelial alpha-mannosidase MAN1C1 in radiation-induced immune cell recruitment - Ségolène Ladaigue; Anne-Charlotte Lefranc; Khadidiatou Balde; Monica Quitoco; Emilie Bacquer; Didier Busso; Guillaume Piton; Jordane Dépagne; Nathalie Déchamps; Nao Yamakawa; Louise Debusschere; Chunxue Han; et al. (iScience, 2022)
Summary: Radiation therapy damages tumors and normal tissues, probably in part through the recruitment of immune cells. Endothelial high-mannose N-glycans are, in particular, involved in monocyte-endothelium interactions. Trimmed by the class I α-mannosidases, these structures are quite rare in normal conditions. Here, we show that the expression of the endothelial α-mannosidase MAN1C1 protein decreases after irradiation. We modeled two crucial steps in monocyte recruitment by developing in vitro real-time imaging models. Inhibition of MAN1C1 expression by siRNA gene silencing increases the abundance of high-mannose N-glycans, improves the adhesion of monocytes on endothelial cells in flow conditions and, in contrast, decreases radiation-induced transendothelial migration of monocytes. Consistently, overexpression of MAN1C1 in endothelial cells using lentiviral vectors decreases the abundance of high-mannose N-glycans and monocyte adhesion and enhances transendothelial migration of monocytes. Hence, we propose a role for endothelial MAN1C1 in the recruitment of monocytes, particularly in the adhesion step to the endothelium.